2007
DOI: 10.1002/aic.11371
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐emulsion based hollow fiber strip dispersion: A novel methodology for gold recovery

Abstract: This article presents the study of Au(I) extraction from synthetic cyanide media through pseudo‐emulsion based hollow fiber strip dispersion (PEHFSD) containing LIX‐79/n‐heptane as extractant in the form of a pseudo‐emulsion with NaOH. The permeation of Au(I) is investigated as a function of various experimental variables: hydrodynamic conditions, feed pH, LIX‐79 concentration in pseudo‐emulsion, cyanide concentration in feed phase, NaOH concentration in pseudo‐emulsion as a strippant, and initial Au(I) concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…In the present case, k m is 3.3 × 10 -5 cm/s, for an estimate D org value of 10 -6 cm 2 /s (10,(13)(14)(15). It should be pointed out that the value of k m is within the magnitude order of membrane mass transfer coefficient found elsewhere (8).…”
Section: Resultssupporting
confidence: 64%
“…In the present case, k m is 3.3 × 10 -5 cm/s, for an estimate D org value of 10 -6 cm 2 /s (10,(13)(14)(15). It should be pointed out that the value of k m is within the magnitude order of membrane mass transfer coefficient found elsewhere (8).…”
Section: Resultssupporting
confidence: 64%
“…Previous literature on SLM with strip dispersion has focused on the removal and recovery of heavy metals such as chromium [13], copper [14], zinc [14], cobalt [14], strontium [15], uranium [16], gold [17], and cadmium [18]. Studies have ranged from lab to pilot plant scales and have demonstrated that SLM with strip dispersion can efficiently remove metals from aqueous solutions, while also recovering them in high concentrations in the aqueous strip solution.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the problem of the contamination of the aqueous feed solution by the emulsion at a higher flow rate (11.66 cm 3 /s), the 5.56 cm 3 /s linear flow rate was selected throughout the study. The importance of pressure control across the tube and shell side hollow fibre contactor in the PEHFSD is also described in a previous publication in which metal separation from different media was carried out [34][35][36].…”
Section: Influence Of the Feed Flow Rate On The Transport Of Cr(vi)mentioning
confidence: 88%